Agrarian legislation of the UPR Directorate - Lubko, Inna (Ukrainian Peasant, 2024)
The purpose of the article is to clarify the essence and significance of the governmental agrarian reform aimed at regulating land relations. The scientific novelty of the research results lies in a comprehensive analysis of the regulatory framework developed for the preparation and implementation of the agrarian reform, which, according to the leaders of the UPR Directory, was intended to alleviate the acuteness of the agrarian issue, to ensure social support of the Directory government by the peasantry, to strengthen the mobilization resource of the UPR army, and to regulate land relations in the countryside. The author’s conclusions. The multidimensionality of the phenomenon of the Ukrainian Revolution of 1917–1921 as a crucial transformational process and a complex socio-political period in which the young Ukrainian statehood was born, despite the powerful array of scientific achievements devoted to various aspects of the revolution, allows us to continue the historical discourse both in the context of understanding the complex, contradictory and dramatic experience of state and nation-building, and in the present times — the battle of Ukraine as a state for its independence and the Ukrainian nation as its creator. Regardless of any political realities or social upheavals, land for the Ukrainian peasantry was the meaning of human existence, its worldview imperative. The architects of political programs and economic innovations realized the importance of the peasant factor in the content of legal acts concerning land as an object of social relations. It was the successful implementation of these acts that determined which side the peasantry would take. The Directory of the Ukrainian People’s Republic, having come to power at the end of 1918, first of all abolished the agrarian legislation of the Hetmanate period and partially restored the laws adopted by the Central Rada. The dynamics of the formation of new agrarian legislation in the difficult internal political conditions associated with the change in the power structure of the UPR, the growing Bolshevik intervention, and the powerful external pressure of the Entente countries was determined by an equally important factor: the need to resolve the agrarian issue. The agrarian legislation developed and implemented by the Directorate was formed by adopting the “Temporary Land Law” of January 18, 1918, and adopting new legislative and bylaw acts (declarations, resolutions, orders, instructions) that provided for a comprehensive approach to land use, rational use and protection of land, institutional and personnel support for agrarian reform, etc. Given the changing political landscape and the economic crisis, which required unpopular decisions, there is a tendency to revise previously adopted regulations. In fact, the principles and approaches to land use are changing, grain procurement is being introduced, and a land tax is being introduced. The relevance of the study of the agrarian legislation of the UPR Directory is determined by the need to comprehend the legal experience of resolving the agrarian issue in the context of its complexity and coherence, or vice versa — its compulsion and contradictions. Taking into account the achievements and miscalculations of predecessors will allow modern lawmakers to improve approaches to comprehensive legislative, organizational and financial support for the mechanism of market turnover of agricultural land and streamlining of the State Land Cadastre.